Pulmonary Giant Cavitary Coccidioides With Fungal Ball and Hemoptysis - Vishal K. Narang MD; Kevin Dao BS; Sara Jaratanian MD; Carlos D'Assumpcao MD; Rasha Kuran MD; Augustine Munoz MD; Arash Heidari MD, FACP, FIDSA (SAGE Publishing, 2022)
Coccidioidomycosis (CM) is a fungal disease that results from inhalation of spores of Coccidioides immitis and C posadasii . If symptomatic, disease primarily manifests as community-acquired pneumonia; however, additional pulmonary manifestations such as pleural effusion, empyema, and cavitation may occur. Diabetic patients have an increased risk of severe and cavitary CM. Cavitary disease may erode vasculature and pulmonary parenchyma leading to further complications. Furthermore, chronic cavities can become colonized as well and develop superimposed infections. This is a case of cavitary CM in uncontrolled diabetic nonadherent to treatment presenting with hemoptysis and mycetoma.